ARHETYPES OF THE LAND AND THE CHILD IN THE PROSE OF THE LITERATURE OF THE UKRAINIAN DIASPORA - Sloniovska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article comprehensively deals with the archetypes of the land and the child in the prose of the Ukrainian diaspora in the 20th-50th of the XXth century.